The Missing Foundation of Mental Preparation: A Cross-Sectional Analysis of Level-2 Mental Skills Use in Indonesian Student-Athletes - Hamid, Muflih Wahid; Angriawan, Tri (Journal of Sport Education, Coaching, and Health (JOCCA), 2025)
This study aimed to examine university athletes’ knowledge and application of Level-2 preparatory mental skills—self-talk, mental imagery, and goal setting—based on Jack Lesyk’s Nine Mental Skills framework, with the expectation that athletes would demonstrate limited conceptual understanding and inconsistent use of these skills due to the absence of structured mental-skills training in their development. Using a cross-sectional survey design, data were collected from 75 purposively selected student-athletes of Universitas Negeri Makassar who were preparing for POMNAS XIX 2025 and had competed in at least one regional-level event. The survey, administered online via Google Forms between 1–10 September 2025, consisted of open-ended items assessing conceptual knowledge and Likert-scale questions (1–5) measuring application frequency during training and competition. Quantitative data were analyzed descriptively, while qualitative responses were interpreted narratively. The results show that self-talk was frequently used in competition (56% “always”) but rarely practiced in training, and 92% of athletes reported engaging in negative self-talk after errors. Mental imagery and goal-setting usage were very low in both contexts, dominated by outcome-oriented visualization and outcome-only goals, with minimal evidence of technical imagery or SMART-based planning. These findings indicate a substantial gap between theoretical expectations and actual practice, suggesting that athletes rely on intuitive and reactive strategies rather than structured psychological preparation. The study highlights the need for integrating systematic mental-skills training into coaching curricula and university sport programs. The paper includes four tables summarizing quantitative and qualitative results.